Completing your evaluation dissertation, thesis, or culminating project - Walser, Tamara M.; Trevisan, Michael S. (Los Angeles, CA : SAGE Publications, Inc., 2021)
Their framework, and this book, is organized by six fundamentals of evaluation practice: quality; stakeholders; understanding the program; values; approaches; and maximizing evaluation use. Throughout the book they use the metaphor of the journey to depict the processes and activities a student will experience as they navigate an evaluation capstone and the six fundamentals of evaluation practice. In pursuit of a completed capstone, students grow professionally and personally, and will be in a different place when they reach the destination and the capstone journey is complete.
Part 1. Essentials for your journey -- Part 2. Navigating the six fundamentals of evaluation practice.
Includes bibliographical references and index.
Keywords: EDUCATIONAL EVALUATION; REPORT WRITING